PENGARUH EXPERIENTIAL MARKETING DAN TOURIST SATISFACTION TERHADAP REVISIT INTENTION TOURISM DI DANAU KELIMUTU - Maria Endang Jamu; Yulius Laga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The objective of the research is to find out the influence of experential marketing and tourist satisfaction positively and significantly to the revisit intention of tourists in the Kelimutu National Park Area. The method used in this study is quantitative descriptive, with respondents in this research were domestic tourists with a total of 140 as a basis for consideration for SEM-PLS. The sample was taken using purposive sampling. The results of the research showed that experential marketing and tourist satisfaction are positive and significant for revisit intention tourist in the Kelimutu National Park.